Development Features of the FSES for Tiered and Continuous Higher Education - A. I. Altukhov; M. A. Skvaznikov; A. A. Shekhonin (Высшее образование в России, 2020)
The article discusses the dynamics of the development of federal state educational standards (FSES) for the preparation of bachelors, masters and specialists in the field of photonics, instrumentation, optical and biotechnological systems and technologies over the past twenty-five years. The authors analyze the features, advantages and disadvantages of tiered and continuous higher education. Particular attention is paid to the development and improvement of state educational standards of higher education in the specialty “Electronic and Optical-electronic Devices and Special-purpose Systems.” The article substantiates the expansion of the scope of professional use of a specialist in the field of electronic and optoelectronic devices and systems and the need to introduce a new – information-analytical type of activity. based on the developed competency models of the results of mastering the educational programs of graduate, undergraduate and specialty studies, a comparative analysis of their orientation in various fields of activity is carried out. One of the main trends in the development of state regulation of training students in an enlarged group of specialties and areas of training “Photonics, Instrumentation, Optical and Biotechnical Systems and Technologies” is providing universities with greater freedom in the development of educational programs and the selection of applied educational technologies. It is shown that the main strategic task of the developer of the main professional educational program is to form a set of competencies that will allow the graduate to work in one of the areas of professional activity. At the same time, this set of competencies should be correlated with some labor functions formally described by professional standards and qualification requirements. It is concluded that the main result of the evolutionary development of educational programs of tiered and continuous higher education was the transition from their academic orientation to a practice-oriented character providing focus on certain professional qualifications and requirements of the employer.